Urinary Essential Elements of Young Children with Autism Spectrum Disorder and their Mothers - Qureshi, Fatir (Res Autism Spectr Disord, 2020)
BACKGROUND: Even though the cause of autism spectrum disorders (ASD) remains unknown, the current understanding points towards complex interactions between environmental and genetic factors. One important environmental factor to consider is intake of toxic and essential elements, and their role in metabolism. Essential elements have received considerably less attention in the literature than the presence of toxins in urine. METHOD: The purpose of this investigation is to comprehensively assess the association between urinary element compositions of 28 mothers who had young children with ASD and 29 mothers who had young typically developing (TD) children, and in a subset of their children (21 with ASD and 26 TD). RESULTS: The results show that there are significant differences between the ASD and TD children cohorts’ concentrations for four specific elements (sulfur, phosphorous, molybdenum, and tin). Utilizing multivariate statistical techniques (Fisher’s discriminant analysis and support vector machines), it was possible to distinguish the ASD from the TD children groups with an 81% accuracy after cross-validation utilizing the four significantly different elements. However, among the mother cohorts assessed, there were no significant differences between those that had children with ASD and those with TD children. There was a significant correlation of levels of phosphorus and sulfur in the children with ASD (r = 0.63, p = 3.0E-3) and in the TD children (r = 0.47, p = 0.02). CONCLUSIONS: Notable differences were observed between the elemental concentration in urine of children with ASD and their TD peers. Analyzing cellular pathways related to these elements are promising areas of future research.